A comparative study of CdS thin films grown on ultra-thin glass substrates by RF magnetron sputtering and chemical bath deposition - Doroody C.; Rahman K.S.; Rosly H.N.; Harif M.N.; Isah M.; Kar Y.B.; Tiong S.K.; Amin N. (Elsevier Ltd, 2023)
Atomic force microscopy; Cadmium sulfide; Chemical analysis; Energy gap; Field emission microscopes; Glass; Hall effect; II-VI semiconductors; Magnetron sputtering; Scanning electron microscopy; Substrates; X ray diffraction; Zinc sulfide; Atomic-force-microscopy; Cadmium sulphide thin films; Chemical-bath deposition; Deposition films; Field emission scanning electron microscopy; Radio-frequency-magnetron sputtering; Sputtered films; Thin glass substrates; Ultra-thin; Ultra-thin glass; Thin films